Thin-film hydrogels with superior stiffness, strength, and stretchability. (May 2020) - Le, Hong Hieu; Tran, Van Tron; Mredha, Md. Tariful Islam; Na, Ju Yong; Seon, Jong-Keun; Jeon, Insu
Abstract: Thin-film polymers and hydrogels show great potential for applications in biomedical and engineering fields. However, owing to their defect sensitivity and weak behavior at micrometer-scale thicknesses, the recently developed thin-film hydrogels have limitations in their mechanical properties that impede their use in actual applications. To overcome these drawbacks, we adopted the hydrophobic–hydrophilic copolymer strategy for fabricating thin-film hydrogels with good mechanical properties using a novel benzene-based bulky hydrophobic monomer. Strong hydrophobic associations and benzene–benzene​ interactions of the hydrophobic-rich hard-phase regions of the copolymer gel imparted high stiffness and strength, and the concomitantly formed hydrophilic-rich soft-phase regions were sacrificed reversibly to achieve high stretchability and toughness. The resulting hydrogel, with a thickness of 550 μ m and ∼ 52 wt% water content, exhibits an excellent Young's modulus (18.03 ± 5.92 MPa), tensile strength (4.3 ± 0.21 MPa), and work of extension (11.85 ± 2.17 MJ/m 3 ). Moreover, our hydrogels show biocompatibility and high stability in different media such as water, seawater, and acidic and physiological solutions. These properties further strengthen their potential for applications in biomedical and engineering fields. Graphical abstract: Highlights: Thin-film hydrogels with excellent mechanical properties were developed. Flexible benzene-based DAAIP monomer was used as the hydrophobic component. AAm was employed as the hydrophilic component. The hydrophobic-hydrophilic copolymer strategy was adopted. The thin-film hydrogels showed biocompatibility and high stability in different media.